Positron Emission Tomography With 18F-Fluorodeoxyglucose in Patients With Sickle Cell Acute Chest Syndrome. Issue 18 (May 2015) - de Prost, Nicolas; Sasanelli, Myriam; Deux, Jean-François; Habibi, Anoosha; Razazi, Keyvan; Galactéros, Frédéric; Meignan, Michel; Maître, Bernard; Brun-Buisson, Christian; Itti, Emmanuel; Dessap, Armand Mekontso; Li., Zhentian
<x xml:space="preserve">Abstract</x> Abstract The acute chest syndrome (ACS) is the main cause of mortality among adult patients with sickle cell disease (SCD). Its pathophysiology is still unclear. Using positron emission tomography (PET) with 18F-fluorodeoxyglucose [18F-fluorodeoxyglucose (18F-FDG)], we explored the relationship between regional lung density and lung metabolism, as a reflection of lung neutrophilic infiltration during ACS. Patients were prospectively enrolled in a single-center study. Dual modality chest PET/computed tomography (CT) scans were performed, with 18F-FDG emission scans for quantification of regional 18F-FDG uptake and CT scans with radiocontrast agent to check for pulmonary artery thrombosis. Regional lung 18F-FDG uptake was quantified in ACS patients and in SCD patients without ACS (SCD non-ACS controls). Maximal (SUVmax) and mean (SUVmean) standardized uptake values were computed. Seventeen patients with ACS (mean age 28.3 ± 6.4 years) were included. None died nor required invasive mechanical ventilation. The main lung opacity on CT scans was lower lobe consolidation. Lungs of patients with ACS exhibited higher SUVmax than those of SCD non-ACS controls (2.5 [2.1–2.9] vs 0.8 [0.6–1.0]; P < 0.0001). Regional SUVmax and SUVmean was higher in lower than in upper lobes of ACS patients (P < 0.001) with a significant correlation between lung density and SUVmax (R2 = 0.78). SUVmean was higher in upper lobes of ACS patients than in lungs of SCD non-ACS controls (P < 0.001). Patients with SUVmax >2.5 had longer intensive care unit (ICU) stay than others (7 [6–11] vs 4 [3–6] days; P = 0.016). Lungs of patients with ACS exhibited higher 18F-FDG uptake than SCD non-ACS controls. Lung apices had normal aeration and lower 18F-FDG uptake than lung bases, but higher 18F-FDG uptake than lungs of SCD non-ACS controls. Patients with higher lung 18F-FDG uptake had longer ICU stay than others.